Improving the Performance of Tax Bailiffs through Understanding the Effects of Job Characteristics, Job Demands, and Compensation - Caecilia Diah Permatasari; Liswandi Liswandi; Yahya Agung Kuntadi (LPPM Universitas Terbuka, 2022)
Purpose - Previous researches generally examined the performances of employee, nurse, lecturer and police officer while only a few of them examined tax bailiff's performance. Therefore the purpose of this research is to determine, analyze and obtain empirical evidence on the effect of job characteristics, job demands, and compensation on tax bailiffs’ performance. Methodology - This is a quantitative research with data collected from 130 tax bailiffs in 63 Tax Offices in Indonesia through questionnaires and analyzed using the Structural Equation Model SMART PLS 3.0. Findings - The results showed that job characteristics and compensation significantly positively affect work engagement. Job characteristics, job demands, and work engagement have a significant positive effect on performance. Meanwhile, job demands insignificantly affect work engagement, and compensation insignificantly affect performance. Originality - This research examined tax bailiffs’ performance which has a broad and significant impact on the achievement of state revenues. It contributes to understanding the relationship between job characteristics, job demands, and compensation on tax bailiffs' performance.